Human apolipoprotein a-i in atherosclerosis. The role of oxidation or natural variants synergizing its dysfunction - Gisonno, Romina Antonela (2020)
Oxidation of human high density lipoprotein and its major proteinapolipoprotein A-I (apoA-I) was proposed to cause their failure toprotect against cardiovascular disease. However, multiple and complex events might contribute to the breakdown of this protein to fulfillits protective role. To set light on this topic, we took advantage of thestudy of a natural variant with a deletion of the lysine 107 (K107del)associated with atherosclerosis and amyloidosis. We oxidized thevariants by controlled incubation with H2O2 and determined structural and biological parameters by biophysical and biological approaches.Both variants oxidized under these conditions preserved or eveninduced an increase in the lipid clearance with respect to untreated proteins (20 % with p ≤ 0.05), and decreased the yield of thephysiological dimeric conformations. Following 30-day incubation at37oC K107del but not Wt acquired a well-defined fibrillar conformation which is the main signature of the amyloid pathology. Theseconformations (but not freshly folded proteins) activated neutrophilsinto the formation of neutrophil extracellular traps (NETs) (p<0.05),which was drastically elicited in the case of the K107del (p<0.001).To initiate the search of possible pathways involved in cellular activation, we tested a cellular model of macrophages. Fresh and oxidized Wt promoted the increase of p62 (p ≤ 0.005), a protein described as anti-inflammatory. In the presence of ATRA (an inhibitorof Nrf2-Keap pathway), only Wt effect was blocked (by 40%). Thus,it may be suggested that the oxidation of apoA-I resulted in the lossof one of its key functions. Altogether, our data support that post translational apoA-I modifications (probably chronic and progressive) raised a protein conformation with significant loss of functionand increased aggregation tendency. Oxidation may help favoringthis conformation. The results learnt here strength a close association between amyloidosis and atherosclerosis.